THE FUNCTIONAL FEATURES OF POLYSEMY IN ENGLISH AND UZBEK LANGUAGES - Nargiza Masharipova (International Journal of Innovative Technologies in Social Science, 2020)
In fact, the emotive potential of the language is high and polysemy is a great advantage to a language, so the article illustrates the varieties of polysemy, structural and functional features of polysemy in translation, differences between the usage and classification of polysemy in Uzbek and English languages. The paper deals with also the problems of translation of polysemy in both languages by using comparative and contrastive analysis of observation.